Pengembangan usaha pada Badan Usaha Milik Gampong (BUMG) dalam pembuatan batu bata tanpa pembakaran di Gampong Seuneubok Baroh Kecamatan Darul Aman Kabupaten Aceh Timur - Faiz Isma; Irwansyah Irwansyah; Heri Irawan (Unri Conference Series: Community Engagement, 2019)
The proposed Program Kemitraan Masyarakat (PKM) will provide solutions to the constraints of BUMG in developing new business units by innovating environmentally friendly and effective bricks without burning. Partners in this case the village BUMG Seneubok Baroh have abundant natural resources, one of which is the availability of clay as a basic ingredient in making bricks without burning. The problem faced by partners now is that BUMG is not running effectively, the lack of knowledge from BUMG managers in utilizing the potential of SDA in developing new businesses that are able to improve the welfare of the village. the methods of service activities used include training and mentoring in the making of new BUMG businesses, ie bricks without burning, provision and training of brick molding tools, website-based e-commerce creation and training and financial application training. The level of achievement can be seen in terms of attitudes, socio-cultural, and economic changes in the target community with the existence of a new business unit for BUMG which has not yet had a business unit, training partners for brick business operations without being burned, training business financial balance and training BUMG admins to managing websites for the promotion of brick businesses.